Sensory acceptability of raw and extruded bovine rumen protein in processed meat products - Conti-Silva, Ana Carolina [UNESP]; Machado Pinto e Silva, Maria Elisabeth; Gomes Areas, Jose Alfredo (Elsevier B.V., 2011)
The use of bovine rumen protein (raw and extruded) as a replacement for extruded soy protein concentrate in three meat products (pork sausage, chicken hamburger, and kibbe) was investigated. Similarity between rumen and soy protein meat products was assessed using triangle tests and sensory acceptability evaluated by consumer panelists using a nine-point hedonic scale. The addition of raw rumen protein was detected in all meat product types tested, while extruded rumen protein was only detected in kibbe. The addition of raw rumen protein decreased the acceptability of pork sausage aroma and flavor, but improved kibbe appearance, texture and overall acceptability. The addition of extruded rumen protein reduced the acceptability of chicken hamburger texture, but improved pork sausage flavor. Replacement of soy protein by bovine rumen protein is feasible based upon sensory results, but depended upon its form and the type of meat product to which it was added. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Bovine rumen protein; Soy protein concentrate; Thermoplastic extrusion; Similarity test; Hedonic scale; Meat product